The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1369/jhc.7a7322.2007
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of Reinnervated Rat Soleus Muscle Is Accompanied by Fiber Transition Toward a Faster Phenotype

Abstract: S U M M A R Y The functional recovery of skeletal muscles after peripheral nerve transection and microsurgical repair is generally incomplete. Several reinnervation abnormalities have been described even after nerve reconstruction surgery. Less is known, however, about the regenerative capacity of reinnervated muscles. Previously, we detected remarkable morphological and motor endplate alterations after inducing muscle necrosis and subsequent regeneration in the reinnervated rat soleus muscle. In the present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 56 publications
(135 reference statements)
0
20
1
2
Order By: Relevance
“…31,42 This slow to fast fiber transition is typically maintained following reinnervation. 33 We did not see a significant shift from Type I to Type II fibers, but among Type II fibers there was a shift toward Type IIa for both the 3-and 6-month denervation groups.…”
contrasting
confidence: 54%
“…31,42 This slow to fast fiber transition is typically maintained following reinnervation. 33 We did not see a significant shift from Type I to Type II fibers, but among Type II fibers there was a shift toward Type IIa for both the 3-and 6-month denervation groups.…”
contrasting
confidence: 54%
“…According to Mendler et al [25], it could also be possible that an initial cross-innervation leads to a persistence of the observed fast fiber type shift.…”
Section: Discussionmentioning
confidence: 98%
“…Following cross-re-innervation (i.e., innervation of slowMHC fibers with ‘fast' motor neurons and innervation of fastMHC fibers with ‘slow' motor neurons), slowMHC fibers tend to express fastMHC and vice versa [19]. Mendler et al [25] found a slow-to-fast fiber type transition in re-innervated soleus and could show a persistent change towards a fastMHC phenotype in regenerated muscles. In contrast, Maatsura et al [17] observed a fastMHC to slowMHC fiber type shift 2 weeks after the trauma, which persisted thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…In the rat soleus muscle, this rapid maturation of myotubes coincides with a switch from expression of embryonic to neonatal myosin heavy chains to adult myosin (Whalen et al 1990). While this change is independent of nerve function, Mendler et al (2008) have shown that, following dennervation and reinnervation, muscle fibers switch from slow-type fibers to fast-type fibers following reinnervation of the muscle fibers (Mendler et al 2008). Furthermore, Gregorevic et al (2004) have demonstrated that these regenerating fibers adopt their fast and slow twitch properties as they regenerate (Gregorevic et al 2004).…”
Section: Importance Of Vascularization Innervation and Mechanical Lomentioning
confidence: 94%